Efficacy of interactive communication system in the management of gestational diabetes - Padmanabhan, Savitha; S, Uma Mageshwari (Eastern Journal of Medical Sciences, 2019)
Background: Gestational Diabetes Mellitus (GDM) is one of the forerunners of diabetes and by its merit demands close surveillance so that early lifestyle changes and preventive programs are instituted. Hence targeted management using effective interactive communication system becomes imperative to combat the phenomenal increase of glucose intolerance in gestation. Methods: The study was conducted at Dr. Seshiah Diabetes Specialties Centre, Chennai and gestational follow-up until delivery was carried out for 900 pregnant women. A diabetes protocol was developed to maintain a complete record of their clinical assessment every month. The clinical management of GDM was done in 3 stages namely during gestation, immediate postpartum and after delivery through effective communication techniques like lecture method, computer-aided counselling, power point presentations, brochures, individual and family counselling, postpartum follow-up through postpartum follow-up module and counselling prospective mothers through audio-visual aids. The impact of dietary intervention given to the pregnant women under follow-up was studied in two folds: Knowledge, Attitude and Practice (KAP) study and estimation of their glycemic level before and after intervention. The glycemic levels before and after intervention was tested for significance level using t test and effect of risk factors on gestational glycemia was tested using multiple regression analysis. Results: The targeted management through interactive counselling and education communication proved effective as maternal glucose was well controlled during gestation and encouraged postpartum screening. Nutrition intervention proved effective in bringing down their energy intake and improved their glycemic level. The post counselling scores in KAP showed significant improvement. Conclusion: GDM may well be incurred in future as an open window of opportunity for prevention, rather than a closed door of bleak outcomes. Increasing awareness of GDM, appropriate timing and methodology of screening, ante partum and postpartum precautionary measures employed through efficient communication strategies in a meaningful way would be a “wake-up” call for the increasing burden of the disease.